1999
DOI: 10.1152/ajpregu.1999.276.3.r652
|View full text |Cite
|
Sign up to set email alerts
|

Central administration of rat IL-6 induces HPA activation and fever but not sickness behavior in rats

Abstract: Interleukin (IL)-6 has been proposed to mediate several sickness responses, including brain-mediated neuroendocrine, temperature, and behavioral changes. However, the exact mechanisms and sites of action of IL-6 are still poorly understood. In the present study, we describe the effects of central administration of species-homologous recombinant rat IL-6 (rrIL-6) on the induction of hypothalamic-pituitary-adrenal (HPA) activity, fever, social investigatory behavior, and immobility. After intracerebroventricular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
70
0
6

Year Published

2001
2001
2020
2020

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 79 publications
(78 citation statements)
references
References 34 publications
2
70
0
6
Order By: Relevance
“…23,38,59 Interestingly, however, one study reported that administration of IL-6 only reduced locomotor activity in the presence of IL-1-beta, while having no effects on it own. 60 Taken together with the results from our study (where TNF-R1-KO animals exhibited unchanged CNS IL-beta responses), these data raise the possibility that additional pathways (such as IL-1) associated with IL-6 (but not primarily involving TNF-alpha) may be responsible for altered locomotor activity in virally infected mice. Indeed, as noted above, IL-1 has been shown to reduce locomotor activity both alone and in combination with IL-6.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…23,38,59 Interestingly, however, one study reported that administration of IL-6 only reduced locomotor activity in the presence of IL-1-beta, while having no effects on it own. 60 Taken together with the results from our study (where TNF-R1-KO animals exhibited unchanged CNS IL-beta responses), these data raise the possibility that additional pathways (such as IL-1) associated with IL-6 (but not primarily involving TNF-alpha) may be responsible for altered locomotor activity in virally infected mice. Indeed, as noted above, IL-1 has been shown to reduce locomotor activity both alone and in combination with IL-6.…”
Section: Discussionsupporting
confidence: 74%
“…Indeed, as noted above, IL-1 has been shown to reduce locomotor activity both alone and in combination with IL-6. [40][41][42]60 Given the critical role played by glucocorticoids in regulating immune responses (especially restraining inflammatory responses), patient populations with altered glucocorticoid signaling as result of reduced hormone or reduced glucocorticoid receptor expression/function, including post-traumatic stress disorder (PTSD) and major depression, may be especially vulnerable to the pathological/behavioral consequences of prolonged exposure to elevated circulating levels of proinflammatory cytokines. Indeed, both of these disorders have been found to be associated with an exaggerated inflammatory responses including increases in plasma concentrations of TNF-alpha and IL-6, and both are associated with increased symptoms of anxiety and alterations in locomotor activity, including psychomotor slowing and fatigue.…”
Section: Discussionmentioning
confidence: 99%
“…Also, mice infected with Ad5mIL6 adenovirus (known to induce excessive IL-6 concentrations over several days) decreased food, water and sucrose intake, novel object exploration, and swimming in the forced swim test [62]. On the other hand, Lenczowski et al [43] reported that i.c.v. IL-6 did not result in changes in social investigatory and locomotor behavior; it reduced the behaviors only when it was administered along with IL-1.…”
Section: Introductionmentioning
confidence: 99%
“…A large amount of evidence identifies IL-6 as a necessary factor for the fever response even though IL-6 by itself is not or only weakly or moderately pyrogenic (Cao et al, 2001;Cartmell et al, 2000;Chai et al, 1996;Harden et al, 2008;Kozak et al, 1998;LeMay et al, 1990;Lenczowski et al, 1999;Nilsberth et al, 2009a;Rummel et al, 2006). However, the origin of IL-6 in immune-induced fever has not been fully identified, although there are reports showing that IL-6 can be produced by a variety of cells in response to different pathological stimuli.…”
Section: Discussionmentioning
confidence: 99%